Teacher –Students Relationship as a Tool for Positive Academic Performance in Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2022)
The paper examined the concept of teacher-students relationship as a tool for positive academic performance. It examined the essential components of student –teacher relationship such as the learners, teachers, cooperative learning, and reciprocal learning and so on. The paper also talks about the importance of teacher-students relationship which stated that good teachers’ students’ relationship creates many advantages between both the teachers and students. For instance, a good relationship produces a good environment within the classroom. It also highlights the causes of poor teachers’ students’ relationship, such as insensitivity to student needs, teachers’ bullying, troublesome behaviour and so on. Lastly, the paper proffers solution to poor teachers’ students’ relationship that, teachers should avoid the use of complete authority in handling students. Since the students are under the care of the teacher, the teacher is expected to show good example to them, his authority and discipline over the students should be personal rather than official and also parents’ show of concern for their children’s welfare is crucial.